A Pre-Experimental Study to Evaluate the Effectiveness of a Planned Teaching Program on Knowledge Regarding the Disposal of Plastic Waste and Its Health Hazards Among Adults in Ghotawde Village of Kolhapur District - Diana Deelip Chinchawadkar (International Journal of Community Health Nursing And Practices, 2026)
Background: Plastics are widely used due to their low cost, durability, and versatility; however, their non-biodegradable nature poses serious environmental and health hazards. Improper disposal of plastic waste contributes significantly to pollution and adverse health outcomes, especially in rural communities where awareness may be limited. This study aimed to assess the effectiveness of a structured teaching program on adults’ knowledge about plastic waste disposal and its associated health hazards in Ghotawde village, Kolhapur district. Objectives: The study sought to evaluate the impact of the teaching program on participants’ knowledge regarding plastic waste disposal and its health risks, as well as to examine the relationship between pretest knowledge scores and selected sociodemographic factors. Methods: A community-based pre-experimental one-group pretest and posttest design was employed. A total of 100 adults were chosen using probability random sampling. Data were gathered through a sociodemographic questionnaire and a structured knowledge questionnaire. After conducting the pretest, the planned teaching program was implemented. Results: The pretest results indicated that 63% of participants had average knowledge, while 37% demonstrated poor knowledge regarding plastic waste disposal and its health hazards. Following the teaching program, all participants (100%) achieved good knowledge levels. The mean knowledge score increased from 9.92 in the pretest to 20.35 in the posttest. The calculated t-value of 24.21 was statistically significant (p
Keywords: Knowledge; adults; health hazards; planned teaching program; plastic waste